Integration of Temperature and Weather Sensors with LORA Technology for Real-Time Monitoring Systems in Basin Cooling Tower - Muhammad Agus Rinaldo; Muhammad Ariandi; Nina Paramytha; Rahmat Novrianda Dasmen (Jambura Journal of Electrical and Electronics Engineering, 2026)
— The cooling system of geothermal power plants (PLTP) critically depends on cooling towers, particularly the basin as the reservoir for cooled water to be recirculated into the system. Real-time monitoring of basin water temperature and weather conditions is essential for maintaining operational efficiency and prolonging equipment lifespan. Manual observation and wired systems are limited in terms of range and response time, prompting the need for a more advanced monitoring solution. This article describes the development and implementation of a LoRa-based monitoring  system that integrates temperature and weather sensors in the cooling tower basin of a geothermal power plant. The research was conducted through literature reviews, direct observation, consultations with experts, and comprehensive field testing of both hardware and software under various operational scenarios. The designed system consistently transmits temperature and weather sensor data with a success rate exceeding 95%, and achieves an effective transmission range of 400–500 meters in open geothermal areas. Implementation of this system results in increased data acquisition speed, improved energy efficiency, and enhanced monitoring accuracy, supporting faster technical responses and better risk management. Evaluation results confirm that the LoRa-based solution functions optimally and is highly applicable for deployment in challenging and remote geothermal industrial environments.